2017
DOI: 10.1504/ijsom.2017.080675
|View full text |Cite
|
Sign up to set email alerts
|

Revealing customer dominant logic in healthcare services

Abstract: Abstract:With the increasing interest in the customers' role in service processes and value creation, there is a need to explore customer dominant logic in real service settings. This study focuses on the appearance and characteristics of customer dominant logic through a case study conducted in a healthcare service organisation. The main findings of the study concern how customer dominant logic appears in certain situations, when the service provider utilises information about a customer's life and ecosystem.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Fourth, this work responds to the call to analyze the cocreation of value from the perspective of the non-referent beneficiaries (Kelleher et al, 2020). The referent beneficiary is the recipient of the service (patient) and has been the predominant perspective in the research on the co-creation of value (Leroi-Werelds, 2019;Seppänen et al, 2017). The cocreation of value of non-referent beneficiaries is important and the emerging literature highlights that it is crucial in situations of vulnerability.…”
Section: Discussionmentioning
confidence: 92%
“…Fourth, this work responds to the call to analyze the cocreation of value from the perspective of the non-referent beneficiaries (Kelleher et al, 2020). The referent beneficiary is the recipient of the service (patient) and has been the predominant perspective in the research on the co-creation of value (Leroi-Werelds, 2019;Seppänen et al, 2017). The cocreation of value of non-referent beneficiaries is important and the emerging literature highlights that it is crucial in situations of vulnerability.…”
Section: Discussionmentioning
confidence: 92%
“…The user-focused perspective takes its starting point in the users’ processes and the user’s own subjective understanding of what is valuable and helpful (Heinonen and Strandvik, 2015; Seppänen et al , 2017). Thus, the user’s goals for engaging with a set of actors and services that form an ecosystem is to enable wellbeing for themselves and for other relevant parties (Heinonen and Strandvik, 2020).…”
Section: Three Perspectives On Ecosystemsmentioning
confidence: 99%
“…While some research has shown that the pairing technique leads to the creativity and innovation of undergraduate students from a variety of majors and classes, including management and business (Nouri et al, 2013;Tadmor et al, 2012), there needs to be more research investigating how pairing contributes to the engagement of management and business students in deriving new ideas and solutions to problems in their field. Researchers have elucidated several issues and problems currently plaguing management in different industries, including education (Das and Mukherjee, 2017;Pors and Ratner, 2017), automobiles Gupta and Singh, 2017), agricultural engineering and natural resources (Najafabadi et al, 2017), the supply chain (Leem and Rogers, 2017), healthcare (Seppänen et al, 2017) and knowledge production (Ayuba and Haynes, 2017). Assigning students to collaborate in dyads or pairs for problem-solving, as an instructional strategy in management higher education, can be applied for generating solutions to problems and issues raised by present management research as illustrated below.…”
Section: Need For Pairing To Foster Creativity and Innovation In The mentioning
confidence: 99%
“…This literature review has highlighted the application of management higher education student dyads to support managers with addressing and solving challenges across the industries of education (Das and Mukherjee, 2017;Pors and Ratner, 2017), automobiles Gupta and Singh, 2017), agricultural engineering and natural resources (Najafabadi et al, 2017), the supply chain (Leem and Rogers, 2017), healthcare (Seppänen et al, 2017) and knowledge production (Ayuba and Haynes, 2017). Before empirical research can be conducted on the salience of management postsecondary student dyads for generating innovative solutions to contemporary management problems, a conceptual model must be developed to explicate how management instructors and faculty can formulate the management higher education student dyads and guide them on engendering creative ideas and innovations for problem-solving in their field.…”
Section: Need For Pairing To Foster Creativity and Innovation In The mentioning
confidence: 99%
See 1 more Smart Citation